The success rate of primary root canal treatment performed by undergraduate students using NiTi rotary instruments: a retrospective study - Yodmanotham, Prattana; Tungsawat, Pakit; Lertnantapanya, Siripat (Mahidol Dental Journal, 2024)
Objective: The aim of this study was to evaluate the success rate and various factors influencing the treatment outcome of primary root canal treatment performed by undergraduate students using NiTi rotary instruments. Material and Methods: A total of 258 out of 379 dental chart records and corresponding radiographic photographs from endodontic treatments conducted from 2014-2019 at the College of Dental Medicine, Rangsit University, were included. Data on patient characteristics comprising age, sex, type of tooth, type of restoration, presence of pre-operative lesions, quality of the coronal restoration, and recall period were collected. Digital periapical radiographs taken before treatment initiation and during recall visits were assessed using the periapical index (PAI). The treatment success was evaluated based on healing criteria, as both the clinical and radiographic presentations were normal. Results The recall period ranged from 6-689 months, with a mean of 15.99 (SD 49.68). The overall recall rate was 68.0%, with a dropout rate of 32.0% (ranging from 6-24 months). The overall success rate was 85.7%, and the healing rate was 10.5%. Significant correlations were found between treatment outcomes and pre-operative lesion presence as well as the quality of the root canal filling (p < 0.001). Additionally, significant correlations were identified between the success and pre-operative lesion presence as well as the quality of the root canal filling. Conclusion: The overall success rate for primary root canal treatment performed by undergraduate students using NiTi rotary instruments was 85.7%. The variable factors that significantly correlate with the success are pre-operative lesion and the quality of the root canal filling.